Livestock marketing studies - Bekure, S.; Tilahun, N. (International Livestock Centre for Africa, 1983)
Examines the need and methods for studying livestock markets and routinely collect time series data on prices of livestock at local, regional and terminal markets, outlining a method for setting up a systematic collection and analysis of livestock market information. Presents a simplifed livestock marketing systems model; illustrated suggestions for data analysis; and recommendations for a national organizational framework for collecting & analyzing livestock market data.